(untitled) (Web of Teachers: Inderscience Research, 2026)
Needs analysis is widely recognized as the cornerstone of English for Specific Purposes (ESP). Unlike General English instruction, ESP is designed to meet clearly defined academic and professional objectives. This article examines the theoretical foundations, types, methods, and pedagogical significance of needs analysis in ESP. Drawing on established scholarship in applied linguistics, the paper argues that systematic needs analysis ensures relevance, enhances learner motivation, supports curriculum design, and promotes alignment between instruction and assessment. The discussion also addresses challenges associated with conducting needs analysis and emphasizes its dynamic and ongoing nature in contemporary educational contexts.